MEMBANGUN BUDAYA KOMUNIKASI YANG EFEKTIF DI LINGKUNGAN SEKOLAH - Jaka Maulana; Evarista Ndawa (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
This community engagement program addresses communication challenges in schools, particularly low confidence in public speaking, lack of understanding of communication ethics, and limited use of digital platforms for organizational communication. Conducted over three days at SMA Negeri 8 Kota Serang, the program applied participatory training in interpersonal communication, public speaking, and digital ethics. The methods included simulation, group discussion, and content creation. Results show a significant improvement in students’ confidence (92%), understanding of ethical communication (78%), and utilization of school digital media (85%). The project produced a draft code of communication ethics and initiated a communication club. These results indicate that training based on values, practice, and digital media is effective in fostering inclusive, ethical, and democratic communication culture in schools.Keywords: school communication, public speaking, communication ethics, interpersonal skills, digital culture